Strategi Dakwah Habib Ja’far dalam Membangun Toleransi Beragama dalam Konten Log In - Alvian Ramadhan (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to analyze the preaching strategy used by Habib Ja'far in building religious tolerance through the "Log In" content. In the digital era, online media has an important role in shaping public opinion and attitudes towards various issues, including interfaith tolerance. Habib Ja'far, as a religious figure who is active on social media, has great potential to influence public views on the importance of living side by side in harmony. This study uses a qualitative descriptive method with a framing analysis approach. Data were collected from the "Log In" video content featuring a dialogue between Habib Ja'far and other religious figures. The results of the study show that Habib Ja'far uses an inclusive preaching strategy, emphasizing the values ​​of kindness, compassion, and tolerance. He also encourages viewers to practice tolerance in everyday life. Through the "Log In" content, Habib Ja'far not only creates an inclusive interfaith dialogue, but also spreads a message of peace and harmony. This study concludes that Habib Ja'far's digital preaching is effective in building interfaith understanding in an increasingly pluralistic society, and has a significant influence on the understanding of religious tolerance among students.